Antepartal and intrapartal fetal monitoring - Murray, Michelle (Michelle L.) (Springer Pub., 2007)
" ... has been one of the major resources in fetal monitoring since its inception ... This book will help move us out of the 20th century and into the 21st."--Doody's Book Review Service. Designed for labor and delivery nurses, nurse midwives, nurses cross-training in L & D, and Ob/Gyn nurses and physicians, this workbook is a step-by-step guide to using the equipment and identifying FHR pattern components and the significance of those components. Everything you need to know to enable you to identify the common signs of fetal well-being and the indicators of fetal compromise are included